Physical Activity Monitoring Preferences in Adults With Bipolar Disorder - Janney, Carol A.; Ducheine, Abigail R.; Reichmann, Robert; Stack, Matthew A.; Fagiolini, Andrea (Frontiers in Psychiatry, 2021)
Introduction Physical activity (PA) monitoring preferences and problems were investigated among adults with bipolar disorder. Methods PARC2 study was conducted at the Western Psychiatric Institute and Clinic at the University of Pittsburgh. This secondary data analysis assessed three PA monitors; Body Media SW Pro Armband, Actigraph AM-7164, and Pedometer Omron HJ-720IT. PA monitors were worn simultaneously for one week. Participants reported preferences and problems (irritating, cumbersome, movement of the activity monitor, technical difficulties, and impaired functioning) encountered with each activity monitor. Results Approximately 70% of the participants were middle-aged Caucasian women with a diagnosis of BD I and overweight. Sixty-six adults with BD wore all 3 monitors simultaneously. Twelve (18%) participants had no PA monitoring preference, 28 (42%) preferred the armband, 17 (26%) preferred the pedometer and 9 (14%) preferred the Actigraph. Two-thirds of participants had at least one problem with at least one activity monitor. Participants reported irritation with the Armband [26%, n=17] and pedometer movement [32%, n =21]. No association was observed between activity monitoring preferences and problems (p=0.72). Conclusion Adults with bipolar disorder were willing to wear PA monitors even though problems were reported. Preference of PA monitors, in descending order, was the armband, pedometer, and Actigraph. The activity monitors selected for investigation included the “gold standard” in activity monitoring (Actigraph) worn at the waist as well as a research grade pedometers that are considerably more affordable, provides activity feedback in real-time, and may be a more feasible option for large scale studies.